Development of Student Worksheet Based on Guided Inquiry Using Articulate Storyline in Fungi Subject Matter for Tenth Grade at SMAN 2 Plus Panyabungan - Fitri Afifah Nst; Endang Sulistyarini Gultom (Universitas Negeri Medan, 2023)
This study aims to determine the feasibility of worksheets based on guided inquiry using Articulate storyline on fungi material. This study uses the ADDIE development model which consists of five steps, namely analysis, design, development, implementation, and evaluation. The results showed that teachers and students needed worksheet so that the worksheet was designed based on guided inquiry. The validation of material experts, learning experts, and design experts are in the very good category with an average score of 96.87%, 96.87%, and 88.46%. The biology teacher's assessment obtained an average of 98.4% which was included in the very good category, and the student response to the worksheet obtained an average of 96.07% which was included in the good category. The product developed is effective in achieving learning indicators on fungi subject matter in terms of the N-gain test with a medium category of 0.65%. So, it can be concluded that worksheet is suitable for use in the learning process.